Policy tool for sustainable rice value chain development in Ghana, used by FAO and AfricaRice - CGIAR Research Program on Rice (2021)
AfricaRice and FAO developed a prospective analysis of rice value chain development with account for environmental impact. The net present value for the growth scenario is USD378 million after investment.